The Effect of Using the STAD (Student Teams Achievement Division) Cooperative Model Assisted by Finger Puppets on Students' Learning Motivation - Sari, Emma; Bulkani, Bulkani; Rahmaniati, Rita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: The ability of students to listen to stories from teachers and then be able to tell them again is not easy, and it will not be as expected. Because students' comprehension abilities vary when receiving and studying the story's content, teachers need a learning model to improve their students' storytelling abilities. In reality, class III students at State Elementary School 5 Pulang Pisau cannot concentrate and are interested in learning using the storytelling method. Aim: This research aims to determine the effect of using the STAD-type cooperative model assisted by finger puppets on motivation to learn Indonesian, especially in improving the storytelling skills of class III students at State Elementary School 5 Pulang Pisau. Method: This research uses a quantitative experimental approach. The research sample comprised 19 class III students at State Elementary School 5 Pulang Pisau. Results and Discussion: The research results show that (1) There is a positive influence that the STAD type cooperative method assisted by finger puppets has on the storytelling skills of class III students because the results Wilcoxon test analysis on all students has a value of Asymp.Sig. (2 Tailed) of 0.000 > 0.05. (2) There is a difference in the average indicator value for students before treatment, namely 13.5, and after treatment, the average value is 24.05. Conclusion: Based on the discussion, it can be concluded that using the STAD-type cooperative method assisted by finger puppet media positively affects students' motivation and storytelling skills.